2013
DOI: 10.1021/la3041852
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Low-Temperature Transformations of Poly(furfuryl alcohol) Deposited on MCM-41

Abstract: MCM-41-type mesoporous silica was used as a support for poly(furfuryl alcohol) deposition. This material was produced by precipitation-polycondensation of furfuryl alcohol (FA) in aqueous slurry of the SiO 2 support followed by controlled partial carbonization. By tuning the FA/MCM-41 mass ratio in the reaction mixture, various amounts of polymer particles were introduced on the inner and outer surface of the MCM support. The thermal decomposition of the PFA/MCM-41 composites was studied by thermogravimetry (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 68 publications
2
10
0
Order By: Relevance
“…The adsorption capacities were calculated from the TPD profiles after their integration. [44,45]. The carbon contents in the studied materials are 1.7 and 29.4 %, respectively, and perfectly correspond to the calculated PFA/MCM-48 mass ratios.…”
Section: Adsorption Capacitysupporting
confidence: 81%
See 1 more Smart Citation
“…The adsorption capacities were calculated from the TPD profiles after their integration. [44,45]. The carbon contents in the studied materials are 1.7 and 29.4 %, respectively, and perfectly correspond to the calculated PFA/MCM-48 mass ratios.…”
Section: Adsorption Capacitysupporting
confidence: 81%
“…mesoporous silica) [42]. For this purpose, polyacrylonitrile (PAN) and poly(furfuryl alcohol) (PFA) have been mainly used due to their high carbon content and thermal stability [43][44][45]. The highest adsorption capacity in the elimination of ketones from the gas phase was achieved for mesoporous silica decorated with small amounts of PFA pyrolysed at 250°C.…”
Section: Introductionmentioning
confidence: 99%
“…The appearance of oxygen-containing groups on the surface of carbonized sample should be connected with the mechanism of decomposition of PFA supported on mesoporous silica and reoxidation of PFA-derived carbonizate. It has been shown that SiO 2 -deposited PFA undergoes structural transformation including some steps such as: opening the furan ring with the formation of γ-diketone moieties and subsequent deeper carbonization resulting in the appearance of higher condensed polyunsaturated graphite-like species containing oxygen groups [29,38]. A part of these functionalities can be stable under carbonization conditions (850ºC, 4 h).…”
Section: Surface Composition Of Cmk-3 (200) Replicamentioning
confidence: 99%
“…Adsorption of gaseous hydrocarbons can easily be improved by covering of silica surface by partially carbonized polymer film [17]. For this purpose, polyacrylonitrile (PAN) and poly(furfuryl alcohol) (PFA) are mainly investigated due to the high carbon content and thermal stability [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies [19] on the adsorption of methyl-ethyl ketone (MEK) vapor on thermally degraded PFA deposited on the MCM-41 silica surface exhibited that the highest adsorption capacity was achieved for the absorbents with low PFA loadings. On the other hand, it was found that calcination temperature played a crucial role in tuning the adsorption properties.…”
Section: Introductionmentioning
confidence: 99%